2022
DOI: 10.1021/acsami.1c23736
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Optimization of the Thermoelectric and Mechanical Properties of Large-Size Homogeneous Bi0.5Sb1.5Te3 Bulk Samples via Carrier Engineering for Efficient Energy Harvesting

Abstract: Manufacturing an economically viable, efficient commercial thermoelectric (TE) module is essential for power generation and refrigeration. However, mediocre TE properties, lack of good mechanical stability of the material, and significant difficulties involved in the manufacturing of large-scale powder as well as bulk samples hinder the potential applications of the modules. Herein, an economically feasible single-step water atomization (WA) is employed to synthesize BST powder (2 kg) by Cu doping within a sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…In order to assess the uniformity, element mapping of Sb and Te was performed using Energy-Dispersive X-ray Spectroscopy (EDS), as shown in Figure 2b,c, confirming the good homogeneity of the material. Based on the Mott formula [47][48][49][50] for a degenerated semiconductor, the Seebeck coefficient could be written as follows:…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to assess the uniformity, element mapping of Sb and Te was performed using Energy-Dispersive X-ray Spectroscopy (EDS), as shown in Figure 2b,c, confirming the good homogeneity of the material. Based on the Mott formula [47][48][49][50] for a degenerated semiconductor, the Seebeck coefficient could be written as follows:…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, element mapping of Pt within the same region confirmed the uniform coating of Pt particles on the surface of the hexagonal sheets, as illustrated in Figure 3e and Table 1. Based on the Mott formula [47][48][49][50] for a degenerated semiconductor, the Seebeck coefficient could be written as follows: The microstructural analysis conducted using FE-SEM and HRTEM provided valuable insights into the morphology and composition of Sb 2 Te 3 coated with Pt nanoparticles. The observations confirmed the regular hexagonal sheet structure of Sb 2 Te 3 and demonstrated the uniformity of the material.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For Sn x BST ( x = 0, 0.04, 0.06) TE ingots, the absolute S value gradually increases and then decreases. To figure out the reason for this phenomenon, when electrons or holes are dominant, under the single parabolic band (SPB) model assumption, the Seebeck coefficient and carrier concentration could be expressed as follows: where F n (η) is the n th Fermi integral, and m *, r , k B , e , T , and η are the effective mass, scattering factor, Boltzmann constant, electron charge, absolute temperature, and reduced Fermi energy (defined as η = ). When acoustic phonon scattering is dominant, r = −1/2.…”
Section: Resultsmentioning
confidence: 99%
“…The lattice parameter calculations indicate a slight decrease in the a value and a marginal increase in the c value for both BST-5 and BST-3 samples upon doping with Cu 2.9 Te 2 , as shown in Figure S1. Previous studies have observed that in the crystal structure of BST, Cu can either substitute on the Bi/Sb site, 5,42,44,47,52,53 or be intercalated in the van der Waals gaps located between quintuple layers. 54 If Cu is intercalated, then the c parameter should increase with the increase in Cu content.…”
Section: ■ Introductionmentioning
confidence: 99%